Staging Molière in Communist Romania. A Quantitative Diorama - PEDESTRU, Mihai (Studia Universitatis Babeș-Bolyai Dramatica, 2023)
This paper accompanies a dataset containing information regarding the stagings of Molière’s plays during the 42 years of the communist regime in Romania, from 1948 to 1989. It offers a quantitative overlook of 120 productions, through statistics and visualizations, in an attempt to make sense of the data and find trends and directions otherwise difficult to detect. The data was collected from a public repertory database, supplemented by information from the theaters’ archives and reviews from period magazines and newspapers. We have strived to let the data ‘speak,’ minimizing speculative commentary to where we felt it was needed to add colour or emphasize certain possible patterns. For network graphing and analysis, we used Gephi 0.9 software, and for the analysis and visualization of geospatial data, QGIS 3. Data processing and graph generation were carried out using Microsoft Excel.